(untitled) (Bioagro, 2020)
Tri-genomic Brassica napus L. was developed by the cross between Brassica napus and Brassica nigra. The crop is an important source of vegetable seed oil in Pakistan, after cotton. The low oilseed rape yield is attributed to high temperature in the production zones. Interspecific hybridization using these two species can be helpful to produce heat resistant hybrids. On the other hand, it has been found that foliar application of different plant growth regulators can be used to reduce the heat stress in Brassica. The objective of this study was to test the response of three different tri-genomic hybrids to high temperature stress at seedling stage. Seedlings were foliar sprayed with 0.13 mM salicylic acid (SA) prior to exposure to high temperature at two true leaf stage. The plants were harvested after 30 days of sowing for growth and biochemical analysis. Plants of V38 showed the highest values for all morphological traits and biochemical activities among the three hybrids. In general, plants exposed to the temperature stress exhibited a significant decline in growth, chlorophyll content and enzyme activity. Foliar application of SA significantly improved leaf and root biomass under heat stress. Further, antioxidative enzyme activities significantly increased in response to SA either compared to control or to plants exposed to temperature stress. It is concluded that application of salicylic acid elevated activity of antioxidative enzymes and was helpful in mitigating the detrimental effects of high temperature in oil seed rape.